Moringa Biscuits: PMT Innovation for Stunting Prevention Alternatives - Sulastri, Sulastri; Akmal, Rifqi; Murfid, Ariq; Muzainah, Muzainah (Universitas Syiah Kuala, 2025)
This community service program aimed to enhance the capacity of Micro, Small, and Medium Enterprises (UMKM) in producing moringa-based biscuits as an alternative Supplementary Food (PMT) to prevent stunting in Aceh. The program involved 20 UMKM participants from Gampong Peurada and Gampong Ceurih, Ulee Kareng, Banda Aceh. The activities were conducted in several stages: preliminary survey and needs assessment, training on moringa flour preparation and biscuit/cracker production, packaging and marketing strategies, and continuous mentoring at each production unit. The training was supported by the provision of equipment to enable participants to produce biscuits independently. Evaluation data were collected using questionnaires and analyzed descriptively. The results showed high participant satisfaction, with 90% stating the training materials met their needs and 85% finding them easy to apply. Competency improvements were recorded in food safety knowledge (80%), moringa flour processing skills (85%), biscuit production capability (90%), and packaging and marketing skills (75%). Furthermore, 75% of participants expressed interest in commercial production, and 80% planned to collaborate with local posyandu in PMT distribution. This program successfully strengthened UMKM skills in producing nutritious, locally-based products while contributing to stunting prevention efforts and promoting local economic empowerment